2022
DOI: 10.48550/arxiv.2205.11653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schur complement dominant operator matrices

Abstract: We propose a method for the spectral analysis of unbounded operator matrices in a general setting which fully abstains from standard perturbative arguments. Rather than requiring the matrix to act in a Hilbert space H, we extend its action to a suitable distributional triple D ⊂ H ⊂ D − and restrict it to its maximal domain in H. The crucial point in our approach is the choice of the spaces D and D − which are essentially determined by the Schur complement of the matrix. We show spectral equivalence between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In order to properly define such a matrix as an unbounded (non-self-adjoint) operator, we follow Section 4 of [18] which specialises a new general framework for the spectral analysis of operator matrices to the particular case of the DWE. Assuming that a, q ∈ L 1 loc (R) with a, q ≥ 0 a.e., let…”
Section: Notation and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to properly define such a matrix as an unbounded (non-self-adjoint) operator, we follow Section 4 of [18] which specialises a new general framework for the spectral analysis of operator matrices to the particular case of the DWE. Assuming that a, q ∈ L 1 loc (R) with a, q ≥ 0 a.e., let…”
Section: Notation and Preliminariesmentioning
confidence: 99%
“…and let D * S be the space of bounded, conjugate-linear functionals on D S . It can be shown that the canonical embeddings D S ⊂ H 2 ⊂ D * S are continuous with dense range, that C ∞ c (R) is densely contained in D S and that D S can also be continuously embedded in H 1 (see [18,Prop. 4.6]).…”
Section: Notation and Preliminariesmentioning
confidence: 99%